2013
DOI: 10.1021/sc4002164
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Solvent-Free Heterogeneous Palladium-Catalyzed Synthesis of Arylamines from Nonaromatic Substrates by Dehydrogenative Alkylation

Abstract: Aldrich, Alfa Aesar and TCI. All reagents were used as received from the chemical company without further purification, excepted for aniline and nitrobenzene which were distilled prior to use. Pd/C (5%) on activated carbon, reduced and dry (Escat 1431) and all the supported catalysts were purchased from Strem Chemicals and Sigma-Aldrich.1 H NMR and 13 C NMR spectra were recorded on a BRUKER DRX 300 or BRUKER ALS 300 ( 1 H 300 MHz, 13 C 75 MHz) in CDCl 3 (except when mentioned) and chemical shifts are given in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 71 publications
(105 reference statements)
0
17
0
Order By: Relevance
“…In addition, Lemaire and co-workers showed that various cyclohexanones could be used as neat substrates to achieve dehydrogenative coupling with amines using Pd/C as the catalyst (Scheme 25C). 46 This method was typically more efficient and selective with 1-octene as a hydrogen acceptor, rather than O 2 , although tetralones underwent coupling in the absence of an acceptor to afford 1-aminonaphthalenes. Collectively, these results represent a valuable application of oxidative dehydrogenation catalysis.…”
Section: Dehydrogenative Coupling Of Cyclohexanones/cyclohexenonesmentioning
confidence: 99%
“…In addition, Lemaire and co-workers showed that various cyclohexanones could be used as neat substrates to achieve dehydrogenative coupling with amines using Pd/C as the catalyst (Scheme 25C). 46 This method was typically more efficient and selective with 1-octene as a hydrogen acceptor, rather than O 2 , although tetralones underwent coupling in the absence of an acceptor to afford 1-aminonaphthalenes. Collectively, these results represent a valuable application of oxidative dehydrogenation catalysis.…”
Section: Dehydrogenative Coupling Of Cyclohexanones/cyclohexenonesmentioning
confidence: 99%
“…2 In many cases, these methods enable synthesis of aromatic compounds with substitution patterns and/or functional groups that are difficult to access via traditional aromatic functionalization reactions. This strategy has been employed by us and others in Pd-catalyzed methods for the conversion of cyclohexanone and cyclohexenone derivatives into substituted phenols, 3 aryl ethers 4 or anilines 5 and for the conversion of cyclohexene derivatives into substituted arenes. 6 More recently, we began exploring methods for aerobic dehydrogenation of partially saturated N -heterocycles to heteroarenes.…”
mentioning
confidence: 99%
“…Heterogeneous Pd catalysts have been successfully used for the dehydrogenation of cyclohexanones and cyclohexenones. 3d,e,4b,5e Other heterogeneous catalysts composed of noble metals (Ru, Au, Pd 3 Pb) have also been shown to be active for aerobic dehydrogenation of the parent 1,2,3,4-tetrahydroquinoline; 17 however, the reactions proceed at high temperatures (>100 °C), they are accompanied by catalyst deactivation, and the results were not extended to substituted tetrahydroquinoline derivatives. During the course of these initial studies, Beller and coworkers reported a unique Co-oxide-based catalyst for aerobic alcohol oxidation (oxidative esterification of primary alcohols).…”
mentioning
confidence: 99%
“…9 Recently, amines were prepared via a hydrogen autotransfer in the presence of a metal catalyst. 21 In order to increase the selectivity of the reaction, the different parameters were modied. 12 Aer an analysis of the literature data, we were curious to notice that the calcium hydride was poorly explored for the reduction of organic functions.…”
mentioning
confidence: 99%